Influence of Malondialdehyde and Matrix Metalloproteinase-9 on Progression of Carotid Atherosclerosis in Chronic Renal Disease with Cardiometabolic Syndrome - Senija Rašić; Damir Rebić; Sabaheta Hasić; Ismar Rašić; Marina Delić Šarac (Mediators of Inflammation)
Objective was to assess whether the concentration of malondialdehyde (MDA) as a marker of lipid peroxidation and serum concentration of matrix metalloproteinase-9 (MMP-9) are involved in the process of atherosclerosis in chronic kidney disease (CKD) patients nondialysis-dependent and those on peritoneal dialysis (PD), both with signs of cardiometabolic syndrome (CMS). Thirty CKD and 22 PD patients were included in a study. All observed patients were divided into three subgroups depending on the degree of atherosclerotic changes in the carotid arteries (CA). Severity of atherosclerotic changes in the CA was evaluated by ultrasonography. We confirmed significantly lower level of serum MDA throughout all the stages of atherosclerosis in PD patients compared with observed CKD patients (P<0.05) and increased serum concentration of MDA and MMP-9 with the progression of severity atherosclerotic changes in both groups of patients. The multiple regression analysis revealed that MDA and MMP-9 are significant predictors of changes in IMT-CA CKD patients (P<0.05) and plaque score on CA in these patients (P<0.05). The results suggest that MDA and MMP-9 could be mediators of CKD-related vascular remodeling in CMS.